Health literacy and health-related behavior in sport among University students in East Java, Indonesia: A cross sectional study - Mochamad Ridwan; Anindya Mar'atus Sholikhah; Bayu Budi Prakoso (Journal Sport Area, 2022)
Health literacy is an important determinant of health outcomes due to its close relation to an individual’s health status and well-being. The purpose of this study is to measure the level of health literacy in university students as well as analyze its relationship with socio-demographic factors and health-related behaviors. A total of 163 university students participated in this study via online-based questionnaires that assessed socio-demographic factors, health-related behavior, physical activity, and health literacy using well-validated instruments. An independent t-test and ANOVA were performed to explore any statistical significance and mean differences in health literacy score. The results discovered no significant differences in demographic characteristics on health literacy scores. However, female respondents, majoring in sport and living in urban areas with parents having higher education degrees, had a slightly higher score than their counterparts. A significant difference in scores was observed in the smoking variable (p = 0.007). Therefore, health literacy in university students is not influenced by demographic characteristics. However, this study showed that higher health literacy scores contribute to better practice of health-related behavior, especially smoking.